Assessment of total body water using bioelectrical impedance analysis in neonates receiving intensive care. Issue 2 (1st September 1997) - Tang, Wing; Ridout, Deborah; Modi, Neena
Abstract : AIMS: To determine the most suitable anthropometric and impedance measures and current frequency for the application of bioelectrical impedance to neonates receiving intensive care; and to derive predictive models for the estimation of total body water. METHODS: Twenty eight babies (median gestational age 30.5 weeks, range 24–38; median birthweight 1.388 kg, range 0.690–3.510) were each studied once during the first week after birth. Total body water was first measured by the method of dilution of isotopic water (H2 18 O). Bioelectrical measurements were made using the tetrapolar surface electrode method from four main distal limb positions (right hand–right foot; right hand–left foot; left hand–left foot; left hand–right foot), the left upper arm–left thigh position and the left scapula–right buttock position, and using six frequencies ((500, 250, 100, 50, 10 and 5 kHz). Regression models, to predict total body water, which were both independent and dependent of body weight on the day of study, were derived. RESULTS: Resistance readings at 50 kHz obtained from the distal limb positions performed best. There was no difference between the distal limb positions. There was no difference in the goodness of fit of the models when using each of three indices of conductor length, foot, spine and sternum. The model total body water (litres) (TBW) = 0.016 + 0.674 bodyweight(kg)−0.038 wt 2 + 3.84 foot length (cm) 2 /resistance (50 kHz in OHMS) performed best, accounting for 99.5% of the variation in TBW, with a 95% prediction interval of 165 ml. The model TBW = 0.144 + 15.518 foot length (cm) 2 /resistance (50 kHz in ohms) accounted for 96.4% of the variation and had a 95% prediction interval of 420 ml. CONCLUSIONS: Bioelectrical impedance analysis is a simple, non-invasive method of estimating total body water in neonates receiving intensive care. It can be applied to both the assessment of changes in body water and body composition.